Beyond the Unconscious : Essays of Henri F. Ellenberger in the History of Psychiatry. - Micale, Mark S. (Princeton legacy library., 2014)
Henri F. Ellenberger, the Swiss medical historian, is best remembered today as the author of The Discovery of the Unconscious (1970), a brilliant, encyclopedic study of psychiatric theory and therapy from primitive times to the mid-twentieth century. However, in addition to this well-known work, Ellenberger has written over thirty essays in the history of the mental sciences. This collection unites fourteen of Ellenberger's most interesting and methodologically innovative historical essays, many of which draw on new and rich bodies of primary materials. Several of the articles appear.